2007
DOI: 10.1523/jneurosci.4975-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

A Forward Genetics Screen in Mice Identifies Recessive Deafness Traits and Reveals That Pejvakin Is Essential for Outer Hair Cell Function

Abstract: Deafness is the most common form of sensory impairment in the human population and is frequently caused by recessive mutations. To obtain animal models for recessive forms of deafness and to identify genes that control the development and function of the auditory sense organs, we performed a forward genetics screen in mice. We identified 13 mouse lines with defects in auditory function and six lines with auditory and vestibular defects. We mapped several of the affected genetic loci and identified point mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(205 citation statements)
references
References 61 publications
7
185
0
1
Order By: Relevance
“…The positions of protein domains were taken from literature sources (Kurima et al, 2002;Delmaghani et al, 2006;Schwander et al, 2007) and confirmed using SMART (Schultz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The positions of protein domains were taken from literature sources (Kurima et al, 2002;Delmaghani et al, 2006;Schwander et al, 2007) and confirmed using SMART (Schultz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…All three genes encode proteins that are expressed in the cochlea and implicated in mammalian hearing, and all have mutant forms that have been linked to non-syndromic hearing loss in humans and/or mice. The proteins Tmc1 and Pjvk have vital roles in hair cell development and function, respectively, whereas Prestin is thought to specifically drive the motility of the outer hair cells on the basilar membrane (Zheng et al, 2000;Marcotti et al, 2006;Schwander et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…66 Pejvakin possibly has an important role in the cell signaling of hair cells and sensory neurons. 67,68 The 352-amino-acid pejvakin protein is translated from a 5 kb cDNA.…”
Section: Genetic Causes Of Nshl In Iran N Mahdieh Et Almentioning
confidence: 99%